2015
DOI: 10.3906/biy-1502-9
|View full text |Cite
|
Sign up to set email alerts
|

Y chromosome genetic diversity and breed relationships in nativePolish cattle assessed by microsatellite markers

Abstract: Cattle provide a wide range of products and services to humans; thus the significance of conservation of livestock genetic resources is evident. We analyzed the genetic variability of five Y-chromosomal microsatellites in 395 bulls representing six cattle breeds (Polish Red, Polish Whitebacks, Polish Red-and-White, Polish Black-and-White, Polish Holstein Friesian, and Simmental). We identified three haplotypes in the paternal gene pool of analyzed populations. Haplotype diversity was low and frequencies ranged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
3
1
Order By: Relevance
“…The overall Y haplotype diversity (0.630 ± 0.027) observed in Indian cattle is reasonably higher than previously reported estimates in Polish cattle (0.037 ± 0.019) 17 , Lidia bovine breeds (0.42) 16 , Continental Europe (0.543 ± 0.026) and Zebu cattle (0.389 ± 0.084) 27 ; but relatively lower than Ethiopian cattle (0.751 ± 0.015) 14 , Creoles (0.779 ± 0.019), Iberian breeds (0.712 ± 0.016) and cattle of Atlantic Islands (0.677 ± 0.037) 27 . Haplotype diversity within lineages as well as retention of allelic variants by various breeds act as a genetic reservoir.…”
Section: Discussion Finding New Haplotypes In Indicine Cattlecontrasting
confidence: 58%
See 1 more Smart Citation
“…The overall Y haplotype diversity (0.630 ± 0.027) observed in Indian cattle is reasonably higher than previously reported estimates in Polish cattle (0.037 ± 0.019) 17 , Lidia bovine breeds (0.42) 16 , Continental Europe (0.543 ± 0.026) and Zebu cattle (0.389 ± 0.084) 27 ; but relatively lower than Ethiopian cattle (0.751 ± 0.015) 14 , Creoles (0.779 ± 0.019), Iberian breeds (0.712 ± 0.016) and cattle of Atlantic Islands (0.677 ± 0.037) 27 . Haplotype diversity within lineages as well as retention of allelic variants by various breeds act as a genetic reservoir.…”
Section: Discussion Finding New Haplotypes In Indicine Cattlecontrasting
confidence: 58%
“…The identification of five single nucleotide polymorphisms (SNPs) has permitted the classification of worldwide extant cattle breeds into three Y-chromosome haplogroups, named Y1, Y2 and Y3 7. The Y chromosome diversity found in indicus cattle is represented by a single haplogroup (Y3) and variability within this haplogroup makes it possible to differentiate paternal lineages between Indian and Chinese cattle 8 and to recognize the presence of Y3b haplotype family of Indian origin exclusively in West African Zebu animal 9 . The Y-specific microsatellite loci have been studied in several cattle breeds from different geographical areas [10][11][12][13] or local breeds such as Ethiopian cattle 14 , Portuguese cattle 15 , Spanish cattle 16 and Polish cattle 17 . The in-depth diversity analyses based on paternal lineages have allowed the identification of several Y-haplotypes within the major haplogroups.…”
mentioning
confidence: 99%
“…Among bovine subpopulations, the highest FST and Nei values (FST = 0.027; Nei = 0.084) were low compared to the results obtained from different studies. In a study conducted in Poland among the Black and White, Polish Black-Backed, and Polish Red populations, FST ranged from 0.247 to 0.941 (Prusak et al, 2015). According to Zatoń-Dobrowolska et al (2007), FST values varied between 0.173 and 0.197 in Red cattle breeds; Nei values were 0.112-0.157.…”
Section: 2020)mentioning
confidence: 99%
“…Ozsensoy and Kurar (2014) examined native Turkish varieties and obtained a 2% variation between populations and 98% within a population. Meanwhile, Prusak et al (2015) showed a 26.5% variation between populations and 73.5% within the population when studying local Polish cattle breeds.…”
Section: 2020)mentioning
confidence: 99%
“…Previous studies reported that the Hd value in bovine Y-chromosome was showed high in Indian Zebu cattle (0.63±0.03) [22], Ethiophian cattle (0.75±0.01) [23], Creoles (0.78±0.02), Iberian breeds (0.71±0.02) and cattle of Atlantic island (0.68±0.04) [24]. Meanwhile, low Hd value in bovine Y- chromosome was showed in Polish cattle (0.04±0.02) [25], Lidia cattle breed (0.42) [26], continental Europe cattle (0.54±0.03) and Zebu cattle (0.39±0.08) [24]. According to ZFY gene, the Pasundan cattle are closed to Taurine lineage.…”
Section: Discussionmentioning
confidence: 95%